A Correlation Study among Reading Habit, Intrapersonal Intelligence and Reading Comprehension Ability - Musdizal Musdizal; Rodi Hartono; Ellen Sepyanti Malana; Herayati Herayati; Okti Wilymafidini (Loquen, 2022)
The purpose of this research was to know the correlation between: (1) reading habit (X1) and reading comprehension ability (Y); (2) intrapersonal intelligence (X2) and reading comprehension ability (Y); and reading habit (X1), intrapersonal intelligence (X2) and reading comprehension ability (Y). This research used quantitative method to collect the data with descriptive correlational design. The population of this research was the fourth semester students of the English Department of IAIN Kerinci which consisted of 44 students as the sample were collected through total sampling technique. In analyzing the data, the researcher used Pearson Product Moment and Multiple Linear Regression technique by using SPSS (Statistical Program for Social Science) 20.0 for windows. It showed that: (1) the coefficient correlation between students’ reading habit and their reading comprehension ability (X1+Y) was 0,867 with a significance value of 0,000 which smaller than 0,05. It indicates that there was very strong positive significant correlation between students’ reading habit and their reading comprehension ability; (2) the coefficient correlation between students’ intrapersonal intelligence and their reading comprehension ability (X2+Y) was 0,576 with a significance value of 0,000 which smaller than 0,05. It means that there was enough positive significant correlation between students’ intrapersonal intelligence and their reading comprehension ability; and (3) the value of significant correlation between students’ reading habit, intrapersonal intelligence and their reading comprehension ability (X1+X2+Y) was 0.000 which smaller than 0.05 (Sig < 0.05). Moreover, the value of simultant test was Fcalculate = 62,472 > Ftable = 2,83. It implies that H3 was accepted and H0 was rejected. In other word, there was significant correlation between students’ reading habit, intrapersonal intelligence and their reading comprehension.